Understanding the Reducibility of CeO2 Surfaces by Proton-Electron Transfer from CpCr(CO)3H - Bunjaku, Osman; Florenski, Jan; Wischnat, Jonathan; Klemm, Elias; Safonova, Olga V; van Slageren, Joris; Estes, Deven P (Inorganic chemistry, 2024)
CeO2 is a popular material in heterogeneous catalysis, molecular sensors, and electronics and owes many of its special properties to the redox activity of Ce, present as both Ce3+ and Ce4+. However, the reduction of CeO2 with H2 (thought to occur through proton-electron transfer (PET) giving Ce3+ and new OH bonds) is poorly understood due to the high reduction temperatures necessary and the ill-defined nature of the hydrogen atom sources typically used. We have previously shown that transition-metal hydrides with weak M-H bonds react with reducible metal oxides at room temperature by PET. Here, we show that CpCr(CO)3H (1) transfers protons and electrons to CeO2 due to its weak Cr-H bond. We can titrate CeO2 with 1 and measure not only the number of surface Ce3+ sites formed (in agreement with X-ray absorption spectroscopy) but also the lower limit of the hydrogen atom adsorption free energy (HAFE). The results match the extent of reduction achieved from H2 treatment and hydrogen spillover on CeO2 in a wide range of applications.CeO2 is a popular material in heterogeneous catalysis, molecular sensors, and electronics and owes many of its special properties to the redox activity of Ce, present as both Ce3+ and Ce4+. However, the reduction of CeO2 with H2 (thought to occur through proton-electron transfer (PET) giving Ce3+ and new OH bonds) is poorly understood due to the high reduction temperatures necessary and the ill-defined nature of the hydrogen atom sources typically used. We have previously shown that transition-metal hydrides with weak M-H bonds react with reducible metal oxides at room temperature by PET. Here, we show that CpCr(CO)3H (1) transfers protons and electrons to CeO2 due to its weak Cr-H bond. We can titrate CeO2 with 1 and measure not only the number of surface Ce3+ sites formed (in agreement with X-ray absorption spectroscopy) but also the lower limit of the hydrogen atom adsorption free energy (HAFE). The results match the extent of reduction achieved from H2 treatment and hydrogen spillover on CeO2 in a wide range of applications.